Cytogenetics of the Simulium arcticum complex (Diptera: Simuliidae) - Shields, Gerald F. (Zootaxa, 2021)
Descriptions of chromosomal rearrangements, geographic distributions and frequencies of nine siblings and 28 cytotypes of the Simulium arcticum Malloch complex are presented. Findings are based on six data sets that include approximately 21,000 chromosomally analyzed larvae from throughout the known geographic range of S. arcticum. This is the largest chromosomal data set for any North American complex of black flies. This summary emphasizes the need to chromosomally analyze taxa of black flies since this type of analysis can result in, not only, a better understanding of the number of taxa in a complex and their relationships but also, it may help to understand the initial stages of reproductive isolation within otherwise morphologically identical groups. Geographically, the streams of eastern Alaska, the entire province of the Yukon and northern Mexico should be sampled. Taxonomically the many cytotypes should be tested for reproductive status when they occur in sympatry with other siblings and cytotypes of the complex. Finally, comparative multi-omic research would be useful.